Neurotechnologies and future warfare - Rickli, Jean-Marc (2021)
With recent developments in emerging technologies such as artificial intelligence and neurosciences, technology is increasingly becoming autonomous and intrusive. The growing reliance of technology as surrogate in warfare raises serious ethical and accountability issues.